Carbon reporting regulation: Real effects, external pressures, and internal policies - Baboukardos, Diogenis; Kopita, Anastasia; Ranegaard, Charlotte; Demetriades, Elias (My University, 2024)
Mandatory climate change reporting is suggested as a mechanism for mitigating firms' climate change impact and, in particular, their carbon emissions. Although extant literature provides evidence of a negative association between the introduction of carbon reporting regulation and firms' carbon emissions, the literature on real effects of climate change reporting regulation is still in its infancy and has yet to provide evidence of the channels through which reporting regulation affects firms' real climate change-related activities. By adopting the theoretical framework of the targeted transparency action cycle, which describes the mechanism leading to the real effects of reporting regulation, we provide empirical evidence on how external pressures exerted on firms and internal policies adopted by them shape the effects of carbon reporting regulation on firms' actual carbon emissions. We take advantage of the 2013 amendments of the UK Companies Act 2006, which made the United Kingdom the first country in the world to require its listed firms to report carbon emissions in their annual reports, and we empirically show that, first, after the introduction of the new reporting regulation, firms exhibit significantly lower levels of carbon emissions; second, these effects are more prominent in firms under higher external pressure; and third, firms that engage with relevant climate change policies exhibit a much larger reduction of their carbon emissions after the regulation took effect.
Keywords: Carbon emissions; Carbon reporting regulation; Climate change policies; Stakeholder pressure; UK